Implementasi Metode Analytical Hierarchy Process Untuk Mendukung Pengambilan Keputusan Dalam Pemilihan Saham - Zhan, Edison (Journal of Digital Ecosystem for Natural Sustainability, 2022)
Investors before investing of course do an analysis first. From the results of the research literature study, generally there are 4 analysis criteria and each criterion has 7 sub-criteria that are used in making stock selection decisions. The 4 criteria are analysis of A.Growth (company income), B.Profitability (ROA and ROE), C.Debt (DER) and D.Share Price (PER and PBV). From the analysis criteria, each company has its own strengths and weaknesses. It is not uncommon for investors to find it difficult to determine the priority weights of the criteria and sub-criteria analysis because investor decisions are subjective, plus there are many stocks available to choose from, so it takes more time and effort in the stock selection process. So we need a decision support system to help investors determine the weight of each criterion and sub-criteria of the analysis so that stock selection can be objective and consistent. This study uses AHP as a method to help make decisions objectively and consistently by carrying out a pairwise comparison matrix process between criteria and sub-criteria and sorting stocks so that they get the best stock priority. The results of the AHP calculation get the priority criteria in sequence, namely B(0.51%), A(0.24%), D(0.17%) and C(0.08%) with a consistency ratio of 0.04. Meanwhile, the priority sub-criteria are 1(0.38), 2(0.24), 3(0.17), 4(0.10), 5(0.06), 6(0.03) and 7(0.02) with a consistency ratio of 0.09. Each consistency ratio below 0.1 means that the weighting for the criteria and sub-criteria is consistent.